Prove the following

Asked by  | 18th Apr, 2010, 01:45: PM

Expert Answer:

(tan22x - tan2x)/(1 - tan22x tan2x) =

Using a2 - b2 = (a+b)(a-b), for numerator and denominator,

[(tan2x - tanx)(tan2x + tanx)]/[(1 - tan2x tanx) (1 + tan2x tanx)] =

= tan3x tanx

Using,

tan (x+y) = (tanx + tany)/(1 - tanxtany)

(tan2x - tanx)/(1 + tan2x tanx) = tan (2x - x) = tanx

and (tan2x + tanx)/(1 - tan2x tanx) = tan (2x+x) = tan3x.

Regards,

Team,

TopperLearning.

 

 

Answered by  | 19th Apr, 2010, 09:30: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.